Web Harvesting: A Technique for Fast Retrieval of Information from Web (International Journal of Engineering and Computer Science, 2017)
VInternet is collection of vast information. Need of searching the web pages for a specific piece of information is a common practice. Search engines are used to search and retrieve the information as per query raised by the user. Making this search process better and fast has always been the area of interest for researchers involved in web mining. The process of searching the web can be improved by Web harvesting. Web harvesting is the process by which specialized software collects data from the Internet and places it into files for end user. It serves a function similar to, but more advanced than, the tasks a search engine performs. Web harvesting is also known as Web scraping. In this article we have explored the field of Web harvesting and emphasized its use for fast and effective retrieval of information from web